Expression of multiple artificial microRNAs from a chicken miRNA126-based lentiviral vector. - Steve C-Y Chen (Public Library of Science (PLoS), 2011)
Background The use of RNAi in both basic and translational research often requires expression of multiple siRNAs from the same vector. Methods/principal findings We have developed a novel chicken miR126-based artificial miRNA expression system that can express one, two or three miRNAs from a single cassette in a lentiviral vector. We show that each of the miRNAs expressed from the same lentiviral vector is capable of potent inhibition of reporter gene expression in transient transfection and stable integration assays in chicken fibroblast DF-1 cells. Transduction of Vero cells with lentivirus expressing two or three different anti-influenza miRNAs leads to inhibition of influenza virus production. In addition, the chicken miR126-based expression system effectively inhibits reporter gene expression in human, monkey, dog and mouse cells. These results demonstrate that the flanking regions of a single primary miRNA can support processing of three different stem-loops in a single vector. Conclusions/significance This novel design expands the means to express multiple miRNAs from the same vector for potent and effective silencing of target genes and influenza virus.